An exploratory review of the relationship between place characteristics and customer’s experience in urban marketplace - Mohd, Siti Zulaikha; Zakariya, Khalilah; Kamaruddin, Zumahiran (2014)
Urban marketplace is a community place where trading activities take place. Over the course of urban development, the marketplace gradually changes and become a place where the communities grow socially, culturally and economically. Consequently, a number of urban marketplaces become iconic because of their unique products and setting, making them a tourist attraction. However, redevelopment projects at times transform the characteristics of the marketplace that eventually affect people’s experience. There is a significant need to closely examine the characteristics of the marketplace to understand how they appeal to people and affect people’s experience. This is important to ensure that the development of sustainable urban marketplace can continue to flourish in the future, alongside their rich heritage values. This paper aims to give an overview of existing studies that have been done on understanding place and place characteristics, the urban marketplace and the dimensions of customers’ experience. The method is carried through an in-depth literature review on the attributes of place characteristics, aspects of the customer’s experience of place and qualities of urban marketplace. The focus of the review is first to understand the concept of place and factors that influence people’s experience in the market. Secondly, this paper discusses the factors that enable the marketplace to sustain the culture and business for the market vendors. The findings from this exploratory review reveal the interconnectedness between the attributes of place characteristics and customers’ experiences that are useful in examining the urban marketplace, which is vital for the local community and visitors.